PENGEMBANGAN VIDEO PEMBELAJARAN MENGGUNAKAN SOFTWARE WONDERSHARE FILMORA PADA PELAJARAN MATEMATIKA MATERI NILAI MUTLAK KELAS X DI SEKOLAH MENENGAH KEJURUAN PADA MASA COVID-19 TAHUN AJARAN 2020/2021 - Anggraeni, Yulia; Arifin, Zaynal; Kurniawan, Dydik; Wahyuningsih, Tri (IAI Al-Mawaddah Warrahmah Kolaka, 2021)
The urgency of this study is an alternative as a solution that can be used for learning during the covid 19 pandemic. This study aims to develop and determine the feasibility of learning video media using Wondershare Filmora Software in absolute value mathematics lessons in class X Multimedia 1 SMK Negeri 20 Samarinda. This research uses Research and Development. The research subjects were 4 media experts, 1 mathematics teacher, and 10 class X students. The object of the research was the development of learning media and the feasibility of learning mathematics videos. Data collection techniques with interviews, and questionnaires. The data analysis technique is descriptive qualitative and quantitative analysis. The results obtained: 1) The process of developing an absolute value mathematics learning video using the R&D (Research and Development) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) on Wondershare Filmora Software, 2) Obtaining the results of a questionnaire from 4 experts media validation obtained a value of 62 very feasible categories and the results of the questionnaire from 1 material validation expert obtained a value of 69 very feasible categories and the results of the questionnaire given to 10 students obtained a score of 59.7 very feasible categories. It can be concluded that the development of learning videos with Wondershare Filmora Software is included in the category of very suitable for use in mathematics learning material for class X Multimedia 1 absolute value at State Vocational High School 20 Samarinda for the 2020/2021 Academic Year.